Analysis of supplier related issues in supply chain practices. (1st January 2011) - Kumar, Darshan; Singh, Om Pal; Singh, Jagdev
Supply chain management (SCM) is regarded as a means to maximise the overall value generated. SCM includes all functions involved in receiving and filling a customer request by forging close relationships with customers and suppliers. Strong relationships and mutual trust between buyer and suppliers are essential for the successful implementation of SCM. This paper is based on the data collected from a survey of 66 Indian textile-related organisations carried out to ascertain issues related to supplier selection and evaluation. The findings indicate that the main criteria for supplier selection in Indian textile organisations are service provided, quality and on-time delivery of material. Effect of supplier selection on performance of organisation and factors influencing development of trust between buyer and suppliers are also discussed.